Purbaya Effect dan Tertib Anggaran Publik dalam Perspektif Agency Theory dan Stewardship Theory - Rina Komala; Layali Ihyani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
Fiscal accountability is a fundamental pillar of good governance, as it is closely associated with transparency, efficiency, and responsible management of public resources. In the Indonesian context, the Purbaya Effect has emerged as a new analytical construct emphasizing fiscal consistency, prudence, and budgetary discipline, aligning with the principle of orderly public budgeting that requires procedural compliance throughout the budgeting cycle. This study aims to examine fiscal accountability through an integrative framework combining Agency Theory and Stewardship Theory. Agency Theory highlights the role of control mechanisms, incentives, and monitoring to address information asymmetry and moral hazard, whereas Stewardship Theory emphasizes trust, integrity, and the moral commitment of public actors. Using a literature review method, this study synthesizes academic literature, fiscal regulations, and relevant empirical findings to develop a comprehensive conceptual framework of fiscal accountability. The results indicate that the integration of formal control mechanisms and intrinsic, public-value-driven motivation leads to more effective, transparent, and sustainable fiscal governance. The study contributes theoretically by enriching public sector governance literature and practically by offering policy recommendations for balancing regulation, oversight, trust, and bureaucratic ethics in fiscal management.